Modeling an automated production control system as part of a reengineering project. (July 2020) - Kukartsev, A V; Tynchenko, S V; Lobkov, K Yu; Fedorova, N V; Stupina, A A; Shamlitskiy, Ya I
Abstract: Nowadays, the operation of production systems common in Russia is no longer relevant. They are already outdated and cannot adequately respond to turbulent global changes, make effective decisions. Also, databases in such systems are isolated and do not interact with other systems. Currently, for enterprises of any industry, automation of information processing and management systems are becoming increasingly relevant. The article presents the project of the enterprise production processes reengineering and its implementation as exemplified by one of the leading enterprises of the Krasnoyarsk Territory, Russia. The procedure includes the development of an automated management system using software products and CASE-tools, the construction of structural-functional models of business processes in AllFusion Process Modeler (BPWin), and simulation using the Arena product. Using the complex of models presented in the article, it is possible to calculate the optimal version of the workflow of the automated control systems under consideration by setting the parameters of the document flow. The introduction of an automated control system allows you to effectively allocate time when processing documents, increase the turnover of funds, and not waste time transferring documents between departments of the branch; less human and material resources are required for the development and maintenance of software. Modeling of production processes reengineering allows us to evaluate the effectiveness of the project before making direct changes in the business-core.